(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2019)
The ability to laser machine materials with high resolution and high throughput is critical in advanced manufacturing for a vast array of applications, from photovoltaic cells to bio-compatible micro-components. Copper bromide (CuBr) lasers with their excellent beam quality promised noticeable advantages and improvements in high precision and material processing at the microscale. The application of the CuBr laser as a precision tool for micromachining of different metals has been demonstrated. That good performance was a result of the combination of high power visible radiation, short pulses, and close to the diffraction-limited laser beam divergence with high-speed galvo scanner beam steering.